The Effect of Subsidiary Characteristics on Efficiency in Knowledge Transfer between Multinational Companies - Cheng, Junshuai; Chelliah, Shankar; Teoh, Ai Ping (Journal of Entrepreneurship, Business and Economics; Vol 9 No 1 (2021), 2021)
This paper aims to establish a comprehensive framework for relationships between parent and subsidiary (subsidiary autonomy, subsidiary position, organizational trust) on knowledge transfer efficiency. Then shed light on how the long-ignored characteristics of the subsidiary (characteristics of the knowledge transfer participant) play a role in the knowledge transfer of MNCs. The study highlights and tests the influence of two parts by subjecting a dataset of 212 Chinese MNCs to a Partial Least Squares Structural Equation Modeling (PLS-SEM) to analysis: one is the impact of relationships between parent-subsidiary (subsidiary autonomy, subsidiary position, organizational trust) on the knowledge transfer efficiency. The other is the subsidiary characteristics (subsidiary age, subsidiary size) moderates the relationship between them. The robust results indicate that subsidiary autonomy, subsidiary position, organizational trust have a significant positive influence on the knowledge transfer efficiency of Chinese MNCs. As well as one of the subsidiary characteristics (subsidiary age) only moderates the relationship between subsidiary autonomy, organizational trust and knowledge transfer efficiency. While the other characteristic (subsidiary size) has no moderation. The findings indicate that the ignored subsidiary characteristics (subsidiary age, subsidiary size) have some moderations in the knowledge transfer efficiency, and it is useful to help MNCs improve knowledge transfer efficiency by copying and creating the implicit meaning of characteristic. Research paper Keywords: Knowledge transfer efficiency; MNCs; Subsidiary characteristics; Subsidiary autonomy;  Subsidiary position; Organizational trust Reference to this paper should be made as follows: Cheng, J., Chelliah, S., & Teoh A. P. (2021). The Effect of Subsidiary Characteristics on Efficiency in Knowledge Transfer between Multinational Companies. Journal of Entrepreneurship, Business and Economics , 9 (1), 230–274.